Project-Based Learning to Enhance Student’s English Skill - Sofiriyah, Nurul Muna; Romadhon, Sahrul; Fatmala, Dewi Nur Rizqi; Ahmad, Terbit Bagaskara (English Education: Jurnal Tadris Bahasa Inggris, 2024)
In today's educational system, the emphasis has switched from the teacher to the student as the primary focal point of the learning process. This study aims to determine the effect of Project-Based Learning on students’ English language skills. The participants of this study were 20 sixth-semester students of English Education in one of the public universities in Central Java. This study used qualitative methods to obtain information and students' opinions about implementing Project-Based Learning to improve their English language skills. In collecting data, the researcher used a questionnaire collected through answers to an online survey to find out and analyze students' opinions. The results of the analysis showed that Project-Based Learning significantly improved students' abilities in terms of personal and interpersonal skills in English. However, the results were unsatisfactory because the researcher also found some problems students complained about when implementing this Project-Based Learning